1998
DOI: 10.1136/gut.43.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Colonic epithelial cell proliferation in hereditary non-polyposis colorectal cancer

Abstract: Background-Despite the recent discovery of four genes responsible for up to 90% of all cases of hereditary non-polyposis colorectal cancer (HNPCC), there will still be families in whom predictive testing is not possible. A phenotypic biomarker would therefore be useful. An upwards shift of the proliferative compartment in colonic crypts is reported to be one of the earliest changes in premalignant mucosa. Aims-To assess the role of crypt cell proliferation as a phenotypic biomarker in HNPCC. Patients-Thirty fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The cause of this regional difference is not clear but may be a result of the specific intraluminal microenvironment of this segment of the colon (microflora, concentration, quality of bile acids, etc). The significance of proliferation within crypt compartment 3 is a matter of some controversy6 34 35 but we and other investigators6 34 feel that this finding represents an expansion of the “normal” proliferative compartment at the base of the crypt (compartments 1 and 2). Even if this expansion does not extend to the mouth of the crypt (compartments 4–5), the non-differentiated cells in this intermediate compartment are probably more exposed to various intraluminal factors than those situated in compartments 1 and 2.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The cause of this regional difference is not clear but may be a result of the specific intraluminal microenvironment of this segment of the colon (microflora, concentration, quality of bile acids, etc). The significance of proliferation within crypt compartment 3 is a matter of some controversy6 34 35 but we and other investigators6 34 feel that this finding represents an expansion of the “normal” proliferative compartment at the base of the crypt (compartments 1 and 2). Even if this expansion does not extend to the mouth of the crypt (compartments 4–5), the non-differentiated cells in this intermediate compartment are probably more exposed to various intraluminal factors than those situated in compartments 1 and 2.…”
Section: Discussionmentioning
confidence: 89%
“…39 Some investigators maintain that such changes are a non-specific finding reflecting the influence of factors such as diet, drugs, age, or methodological flaws. In support of this, Green and colleagues35 have shown that there is no increase in the somatic mutation rate in the normal mucosa of patients with HNPCC 40. However, increased stem cell somatic mutation in the non-neoplastic colorectal mucosa has been described in both familial adenomatous polyposis and Crohn's disease 41.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Such observation indicates that an upward shifting of the proliferation process does occur in the sigmoid tract of diverticular disease patients. This would appear as a relevant finding, as an upward expansion of the proliferating compartment towards the luminal surface of the crypt has been regarded as a meaningful event, non‐differentiated cells being dangerously exposed to possible carcinogenetic intraluminal factors 22, 23 . Intriguingly, such upward shifting has been also shown in the colonic mucosa of patients at high risk of colon cancer as those with large adenomas 24 .…”
Section: Discussionmentioning
confidence: 94%